An Analysis of the 2021 Apologies by the Royal Society of Tasmania and the Tasmanian Museum and Art Gallery to the Tasmanian Aboriginal Community. Issue 1 (2nd January 2023) - Rimmer, Zoe; Taylor, Rebe
Abstract : In 2021, the Royal Society of Tasmania and the Tasmanian Museum and Art Gallery (TMAG) apologised to the Tasmanian Aboriginal Community for past wrongs. The mistreatment of Tasmanian Aboriginal Ancestral remains by the Society in the nineteenth century is well known. Less well known is that the Society, in association with TMAG, removed Ancestral remains and cultural objects from Country until the late twentieth century and actively resisted early claims for repatriation. Were the Apologies comprehensive? How did Aboriginal Community representatives respond to them? This article analyses the Apologies in consideration of the authors' recently published report to inform the Society's Apology, and the wider context of truth-telling efforts in Australia.